Social Interaction and Performance of Third-Year Students in Geometry - Mildin J. Retutas (JPAIR Institutional Research Journal)
Social interaction creates a vital source of opportunities to learn Mathematics and opportunities for students to talk about their own thinking, and this talk encourages reflection. A study was organized to find out the relationship between the social interaction and the performance of third-year students in geometry. Specifically, the study sought to determine their levels of accidental, repeated, regular, and regulated social interactions; students'academic performance in geometry; and the relationship between students'levels of social interaction and their performance in Geometry. The study used the descriptive-correlation method involving 39 students as respondents, and complete enumeration sampling design was used. The descriptive used for social interactions were outstanding, very satisfactory, satisfactory, poor and very poor while for the performance were very high, high, moderate, low and very low. The results showed no significant relationship with the social interaction, while the students'performance in geometry was very satisfactory. The study concludes that the social interaction has no influence on the performance of students in geometry. The study recommends further study shall be made on the relationship of the students'performances when clustered according to the different levels of social interaction so that appropriate intervention can be made easily.